Pengaruh Sosial Media Marketing, Online Customer Review dan Brand Image terhadap Keputusan Pembelian pada Jiniso.Id pada Tiktok Shop di Kota Batam - Simamora, Anita Romauli; Evyanto, Winda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The rapid growth of digital platforms has transformed consumer purchasing behavior, particularly on social commerce platforms like TikTok Shop. Jiniso.id, a local fashion brand operating on TikTok Shop in Batam City, faces challenges such as low visibility of marketing content, inconsistent customer reviews, and a weak brand image. This study aims to examine the influence of social media marketing, online customer reviews, and brand image on consumers’ purchasing decisions toward Jiniso.id products. A quantitative descriptive approach was adopted, using purposive sampling to survey 100 respondents who had previously purchased products from Jiniso.id via TikTok Shop. Data were collected using structured questionnaires and analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing (t-test and F-test). The findings reveal that social media marketing contributes 22.6%, online customer reviews contribute 34.3%, and brand image contributes 30.0% to purchasing decisions. Together, these three variables account for 78.3% of the variance in consumer purchase decisions. The statistical results confirm that each factor has a significant and positive effect on purchasing decisions, both individually and collectively. These findings highlight the importance of digital marketing optimization, review credibility, and brand consistency in enhancing consumer trust and decision-making on social media-based commerce platforms.